2019
DOI: 10.3390/en12050924
|View full text |Cite
|
Sign up to set email alerts
|

Daily Operation Optimization of a Hybrid Energy System Considering a Short-Term Electricity Price Forecast Scheme

Abstract: The scenario where the renewable generation penetration is steadily on the rise in an increasingly atomized system, with much of the installed capacity “sitting” on a distribution level, is in clear contrast with the “old paradigm” of a natural oligopoly formed by vertical structures. Thereby, the fading of the classical producer–consumer division to a broader prosumer “concept” is fostered. This crucial transition will tackle environmental harms associated with conventional energy sources, especially in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Based on this equation, energy demand by prosumer and consumer load as well as charging energy of ESSs should be equal to the energy supplied by RESs and discharging energy of ESSs. According to (10)(11), exchanges power with the grid (P E t ) is constrained to maximum and minimum values of allowable power which the EP is permitted to export or import.…”
Section: Optimization Constraintsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this equation, energy demand by prosumer and consumer load as well as charging energy of ESSs should be equal to the energy supplied by RESs and discharging energy of ESSs. According to (10)(11), exchanges power with the grid (P E t ) is constrained to maximum and minimum values of allowable power which the EP is permitted to export or import.…”
Section: Optimization Constraintsmentioning
confidence: 99%
“…Electricity price prediction is considered as critical information for electricity market participants and decision-makers. Although several methodologies have been proposed for the electricity price forecasting, which mostly differs in the model selection, data preprocessing, testing and calibration steps, the literature is limited in the field of electricity price prediction [10,11]. The principal reason for the limited work's roots in monopoly basis of electricity supplying systems, which has resulted in limited or absence of competition in electricity markets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A life cycle cost analysis was also presented in their study with break-even point calculation for the hybrid solar water heating system. Bento et al [10] proposed an optimized control strategy for hybrid energy systems which contains photovoltaics, pumped-storage hydropower, and wind power under different scenarios. A hybrid energy system with grid-connection in Mali was optimized using HOMER software [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been indicated that, in the second half of this century, their contribution might range from 20% to more than 50% once we establish the correct government policies [2]. That has encouraged a large number of studies, mainly in the photovoltaic energy field [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%